Pension Incentives and the Retirement Decisions of Couples - Kadir Atalay; Garry Barrett (Institute for the Study of Labor (IZA), 2016)
Recent reforms to social security in many countries have sought to delay retirement. Given the family context in which retirement decisions are made, social security reforms have potentially important spill-over effects on the participation of spouses. This paper analyses the impact of women's pension incentives on the retirement decision of their husband. The 1993 Age Pension reform in Australia increased the eligibility age for Age Pension benefits for women. This reform caused an increase in participation of men married to women in the affected cohorts. The behavioral responses are due to wealth effects and preferences for shared leisure.
Keywords: D91; I38; J26; 330; retirement; age pension; joint retirement; spousal effect